2019
DOI: 10.1007/s12550-019-00375-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential adverse effects on animal health and performance caused by the addition of mineral adsorbents to feeds to reduce mycotoxin exposure

Abstract: The contamination of feed with mycotoxins is a continuing feed quality and safety issue, leading to significant losses in livestock production and potential human health risks. Consequently, various methods have been developed to reduce the occurrence of mycotoxins in feed; however, feed supplementation with clay minerals or mineral adsorbents is the most prominent approach widely practiced by farmers and the feed industry. Due to a negatively charged and high surface area, pore volume, swelling ability, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 128 publications
(133 reference statements)
3
68
1
1
Order By: Relevance
“…Modified adsorbents are prepared by alteration of surface properties such as cation exchange capacity using acids, alkalis, organic compounds and heat, that consequently increase their contaminant removal capacity and efficacy [44]. Nevertheless, their safety and interaction with nutrients and veterinary substances remain a concern [45].…”
Section: Resultsmentioning
confidence: 99%
“…Modified adsorbents are prepared by alteration of surface properties such as cation exchange capacity using acids, alkalis, organic compounds and heat, that consequently increase their contaminant removal capacity and efficacy [44]. Nevertheless, their safety and interaction with nutrients and veterinary substances remain a concern [45].…”
Section: Resultsmentioning
confidence: 99%
“…Inorganic (clay minerals), organic (yeast cell wall and glucomannan) feed additives as well as microorganisms and enzymes are added to feed, with the sole aim of binding, inactivating or detoxifying mycotoxins, to reduce their bioavailability in farm animals [62]. Nevertheless, recently, Elliott et al [63] showed that some of these substances, particularly clay minerals, may cause a wide range of negative health effects in farm animals, including an interaction with micronutrients and veterinary substances. Moreover, other researchers have reported inefficiencies of most commercial binders or detoxifiers, as well as their affinity for only a single mycotoxin [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, not to disregard the potential negative effects, grape seeds and seabuckthorn have been ascribed to possess beneficial properties in both humans and animals [ 14 , 15 , 52 , 53 ]. Moreover, while it is generally assumed that the involved mechanism is physisorption [ 54 , 55 ], the adsorption process is also influenced by the chemical properties and interactions between the adsorbents and mycotoxins [ 54 , 56 ]. Similar studies reported the importance of surface conformation and chemical composition in relation to the interactions between adsorbent functional groups and mycotoxin molecules under acidic conditions [ 27 , 33 , 56 ].…”
Section: Resultsmentioning
confidence: 99%